Association of glutamate receptor gene polymorphisms with attention-deficit hyperactivity disorder susceptibility: a systematic review and meta-analysis - Zou, Dehua; Zeng, Qiaoli; Liu, Pei; Wei, Yue; Guo, Runmin; Zhu, Yizhun; He, Rong-Rong (Frontiers in Genetics, 2024)
Background: There is a growing body of evidence indicating a possible association between genetic variations and attention-deficit hyperactivity disorder (ADHD), although the results have been inconsistent. The objective of this study was to evaluate the correlation between the GRIN2A, GRIN2B and GRM7 gene polymorphisms and ADHD. Methods: A comprehensive meta-analysis and subgroup evaluation was conducted using a fixed-effects model to analyze the association between ADHD and GRIN2B (rs2284411), GRIN2A (rs2229193), and GRM7 (rs3792452) in six genetic models (dominant, recessive, overdominant, homozygous, heterozygous, and allele models). Results: The meta-analysis comprised 8 studies. The overall analysis showed that the GRIN2B rs2284411 T allele and T carries were significantly associated with a decreased risk of ADHD (dominant model:TT + CT vs. CC: OR = 0.783; 95% CI: 0.627–0.980; p = 0.032, allele model:T vs. C: OR = 0.795; 95% CI: 0.656–0.964; p = 0.019), especially in the Korean subgroup (dominant model:TT + CT vs. CC: OR = 0.640; 95% CI: 0.442–0.928; p = 0.019, overdominant model: CT vs. TT + CC: OR = 0.641; 95% CI: 0.438–0.938; p = 0.022, allele model:T vs. C: OR = 0.712; 95% CI: 0.521–0.974; p = 0.034 and heterozygous model: CT vs. CC: OR = 0.630; 95% CI: 0.429–0.925; p = 0.018). However, no meaningful associations were found for rs2229193 and rs3792452. Conclusion: The results of the meta-analysis provide strong evidence that the rs2284411 T allele is significantly associated with reduced susceptibility to ADHD, particularly in the Korean population.